2016
DOI: 10.18632/oncotarget.8843
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic combination of DT-13 and topotecan inhibits human gastric cancer via myosin IIA-induced endocytosis of EGF receptor in vitro and in vivo

Abstract: Combination therapy has a higher success rate for many cancers compared to mono-therapy. The treatment of Topotecan (TPT) on gastric cancer (GC) is limited by its toxicity and the potential drug resistance. We found that the combination of the saponin monomer 13 from the dwarf lilyturf tuber (DT-13), performing anti-metastasis and anti-angiogenesis effects, with TPT synergistically induced apoptotic cytotoxicity in GCs with high EGF receptor (EGFR) expression, which was dependent on DT-13-induced endocytosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…NM IIA was essential for the endocytosis of EGFR and the modulation of the EGFR‐dependent activation of downstream signals, including ERK1/2 and AKT . In our previous research, we further confirmed the relationship of NM IIA and EGFR and that the ability of DT‐13 to enhance the pro‐apoptotic effect of TPT on GC via myosin IIA‐induced endocytosis of EGFR in vitro and in vivo . Meanwhile, it had been reported that EGFR signalling was also associated with increased glycolysis: activated the first step in glycolysis .…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…NM IIA was essential for the endocytosis of EGFR and the modulation of the EGFR‐dependent activation of downstream signals, including ERK1/2 and AKT . In our previous research, we further confirmed the relationship of NM IIA and EGFR and that the ability of DT‐13 to enhance the pro‐apoptotic effect of TPT on GC via myosin IIA‐induced endocytosis of EGFR in vitro and in vivo . Meanwhile, it had been reported that EGFR signalling was also associated with increased glycolysis: activated the first step in glycolysis .…”
Section: Introductionsupporting
confidence: 75%
“…In our previous study, we had found that DT‐13 combined with TPT showed stronger antitumour effect in mice subcutaneous xenograft model in vivo compared with their individual effects . Here, we further evaluated the effect of DT‐13‐TPT combination in vivo using an established BGC‐823 cell orthotopic xenograft model.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…24 Apoptotic cells in tumor tissues were determined by TUNEL BrightGreen Apoptosis Detection Kit (Vazyme Biotech Co., Ltd), according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%